Derivational Suffixes Found in “Confessions of a Shopaholic” Novel by Sophie Kinsella - Arniati Rambu Ana Awa; I Komang Sulatra; I Made Iwan Indrawan Jendra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
This research focused on analysing the derivational process of suffixation found in the novel entitled “Confessions of a Shopaholic.” Observation and qualitative method were applied in this study. Observation method used in collecting the data. The steps of colleting the data were first, reading the novel carefully, second finding and listing all complex words that contains derivational suffixes, then identifying and classifying the derivational suffixes. Meanwhile, qualitative method used to analysing the data. There were two steps in analysing the data, namely identifying and describing the data by using some words and presented by using tree diagram. This research used theory from Plag (2002) and supported by theory from McCharty (2002). The result of this research shows that there are some derivational suffixes found in the data source. They are suffixes –ment, -ion/-ation, -er/or, -ance, -ist, -ism, -ing, -hood, -ity, -(e)ry, -ant, -ful, -ship, -ize, -able/-ible, -less, -al/-ial/-ual, -ive/-ative, -ish, -ic, -ary, -ous, ed, and –ly. These suffixes are divided into four classes of suffixation namely, noun maker, verb maker, adjective maker and adverb maker.